Neonatal Alcohol Exposure in Mice Induces Select Differentiation- and Apoptosis-Related Chromatin Changes Both Independent of and Dependent on Sex - Schaffner, Samantha L.; Lussier, Alexandre A.; Baker, Jessica A.; Goldowitz, Dan; Hamre, Kristin M.; Kobor, Michael S. (Frontiers in Genetics, 2020)
Prenatal alcohol exposure (PAE) affects many aspects of physiology and behaviour, including brain development. Specifically, ethanol can influence expression of genes important for brain growth, including chromatin modifiers. Ethanol can also increase apoptotic cell death in the brain and alter epigenetic profiles such as modifications to histones and DNA methylation. Although differential sex outcomes and disruptions to the function of multiple brain regions have been reported in fetal alcohol spectrum disorder (FASD), the majority of our knowledge on molecular epigenetic and apoptotic dysregulation in PAE is based on data from males and is sometimes limited to assessments of the whole brain or one brain region. Here we examined histone modifications, DNA methylation, and expression of genes involved in differentiation and proliferation related-chromatin modifications and apoptosis in the cerebral cortex and cerebellum of C57BL/6J mice exposed to an acute alcohol challenge on postnatal day 7, with a focus on differential outcomes between sexes and brain regions. We found that neonatal alcohol exposure altered histone modifications, and impacted expression of a select few chromatin modifier and apoptotic genes in both the cortex and cerebellum. The results were observed primarily in a sex-independent manner, although some additional trends toward sexual dimorphisms were observed. Alcohol exposure induced trends toward increased bulk H3K4me3 levels, increased Kmt2e expression, and elevated levels of Casp6 mRNA and bulk γH2A.X. Additional trends indicated that ethanol may impact Kdm4a promoter DNA methylation levels and bulk levels of the histone variant H2A.Z, although further studies are needed. We comprehensively examined effects of ethanol exposure across different sexes and brain regions, and our results suggest that major impacts of ethanol on bulk chromatin modifications underlying differentiation and apoptosis may be broadly applicable across the rodent cortex and cerebellum in both sexes.